Domain-specific character of tonal cognition and its consequences for the semiotics of music - Podlipniak, Piotr (Interdisciplinary Studies in Musicology, 2014)
The experience of tonal relations elicits different emotions of stability in listeners. Thus, tonality can be understood as a tool of emotional communication. For many semioticians every communicative phenomenon should be explained in terms of the sign theory. However, the pre-conceptual character of emotions of stability raises doubts about the applicability of a semiotic framework as a means of interpreting tonality. According to the author’s opinion, the applicability of a semiotic framework in music research is useful only if there is a single system for generating meaning in the brain, which is engaged in the processing of all kinds of meanings in language, music, and other communicative phenomena. Both music and language are complex phenomena which, in fact, share many communicative mechanisms. Nevertheless, they also possess traits which are specific solely to each. If the evolution of music and language branched out at some point in the anthropogenesis, some of music’s communicative features (among them tonality) would have become domain-specific. This means that the interpretation of a tonal message is based on another rule, and not the one involved in the interpretation of meaning in language. Thus, interpreting the message of tonality in terms of the semiotic sign theory is not a legitimate procedure. From this point of view, the only way of applying the semiotic framework to research into tonality is to understand signs in a purely functional sense, independent of the process of interpretation. Such an understanding of signs necessitates, however, a reformulation of semiotics.